SDL 2015: Model-Driven Engineering for Smart Cities : 17th International SDL Forum, Berlin, Germany, October 12-14, 2015, Proceedings - Fischer, Joachim; Scheidgen, Markus; Schieferdecker, Ina.; Reed, Rick.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 17th International System Design Language Forum, SDL 2015, held in Berlin, Germany, in October 2015. The 15 full papers and 4 short papers presented in this volume were carefully reviewed and selected from 26 submissions. They are organized in topical sections named: smart cities and distributed systems; specification and description language; domain specific languages; goal modeling; use-case modeling; and model-based testing.
Keywords: Software engineering; Logic design; Computer science; Information Systems; Computer network architectures; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Management of Computing and Information Systems; Computer Systems Organization and Communication Networks